SIRT7 Regulates the Vascular Smooth Muscle Cells Proliferation and Migration via Wnt/β-Catenin Signaling Pathway. (4th December 2018) - Zheng, Jianghua; Chen, Kai; Wang, Haifei; Chen, Zhilong; Xi, Yong; Yin, Hongshun; Lai, Kun; Liu, Yujuan
Abstract : A huge amount of evidence indicates that sirtuin 7 (SIRT7), a key mediator of many cellular activities, plays a crucial role in the pathogenesis of various diseases. However, little is known about the role of SIRT7 in atherosclerosis. This study investigated the potential role of SIRT7 in regulating the proliferation and migration of human vascular smooth muscle cells (HAVSMCs) and its possible molecular mechanism. In this study, human vascular smooth muscle cells (HAVSMCs) were induced by oxidized low-density lipoprotein (ox-LDL) to establish atherosclerosis (AS) cell model. Immunofluorescence staining and Western blot were used to detect the level of α -SMA expression, which was a marker protein in AS. In addition, RT-qPCR and Western blot assay were applied for exploring the mRNA and protein expression levels of SIRT7, Wnt, β -catenin, and cyclin D1 after knockdown or overexpression of SIRT7. And, furthermore, Cell Counting Kit-8 assay, flow cytometry, and wound-healing assay were used to assess HAVSMCs proliferation, cell cycle, and migration. Dickkopf-1 (DKK-1), a secretory glycoprotein that can block Wnt/ β -catenin pathway, was used in SIRT7 overexpression HAVSMCs; subsequently cells proliferation and migration were assessed by Cell Counting Kit-8 assay, flow cytometry analysis, and wound-healing assay. We found that knockdown of SIRT7 significantly promoted cell proliferation and migration, decreased the percentages of cells in the G1 and G2 phases, and increased those in the S phase and downregulated the protein expression levels of Wnt, β -catenin, and cyclin D1, while overexpression of SIRT7 had reverse results. After treatment with Wnt/beta-catenin pathway inhibitor DKK-1 in SIRT7 overexpression HAVSMCs, cell proliferation and migration were increased, respectively. In conclusion, SIRT7 inhibited HAVSMCs proliferation and migration via enhancing Wnt/ β -catenin activation, which provided a novel therapeutic strategy for antiatherosclerosis.